2015
DOI: 10.1213/ane.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pain-Like Behaviors Are More Sensitive to Morphine and Buprenorphine Than Mechanically Evoked Behaviors in a Rat Model of Acute Postoperative Pain

Abstract: The present study demonstrates that a hindpaw plantar incision induces SFL behaviors in rats and that these behaviors have higher bioassay sensitivity to analgesic interventions with morphine and buprenorphine compared with mechanically evoked behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
21
1
Order By: Relevance
“…Surgery consisted of a 20 mm longitudinal incision made through the skin and fascia of the plantar hind paw as previously described. 23 , 25 The flexor digitorum brevis muscle was then elevated, stressed, and incised longitudinally with the muscle origin and insertion remaining intact. The skin was closed with two mattress 5–0 silk sutures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery consisted of a 20 mm longitudinal incision made through the skin and fascia of the plantar hind paw as previously described. 23 , 25 The flexor digitorum brevis muscle was then elevated, stressed, and incised longitudinally with the muscle origin and insertion remaining intact. The skin was closed with two mattress 5–0 silk sutures.…”
Section: Methodsmentioning
confidence: 99%
“…A rat model of incisional pain has been extensively characterized, which includes behavioral phenotypes, nociceptor sensitization, and pharmacologic modulation. 20 25 Additionally, our lab and others have reported that intra-plantar infiltration of capsaicin attenuates spontaneous pain behaviors and heat hyperalgesia. 26 , 27 This phenomenon provides a unique opportunity to identify neural transcriptomes that are specifically induced during incisional pain.…”
Section: Introductionmentioning
confidence: 95%
“…Spontaneous foot lifting was used as a measure of spontaneous pain as described previously (Kabadi, Kouya, Cohen, & Banik, 2015). Animals were placed in individual Plexiglas chambers on a mesh floor above an angled mirror and habituated for 30 min to minimize exploratory behaviour during the assessment period.…”
Section: Methodsmentioning
confidence: 99%
“…One week later, 3 doses of buprenorphine were administered, one at the beginning of the experiment, and then after 12 and 24 hours. The dose and interval of buprenorphine is midrange for what is commonly used for postoperative pain control (Kabadi, Kouya, Cohen, & Banik, 2015), and is considered to have an effective duration of action of 12 hours.…”
Section: Methodsmentioning
confidence: 99%